Wczesnochrześcijańskie ruchy paramonastyczne na podstawie Diversarum hereseon liber Filastriusza z Brescii oraz innych katalogów herezji - Szram, Mariusz (Vox Patrum, 2018)
The catalog of the heresies of Filastrius of Brescia, like other early Christian collections of informations about heterodox movements at the time, testifies the existence of groups characterized by excessively rigorous asceticism. Their description is the subject of the article. Most of these unorthodox paramonastic movements were based on the Gnostic and Manichean assumptions. The groups that accentuated the exaggerated role of prayer, among which the Messialians were the leaders, have gained wide coverage. Descriptions of their activities take up a lot of space in the early Christian catalogs of heresies, especially in the case of John of Damascus. Filastrius, however, for some reason misguided the activity of the Messalians. This fact requires a careful treatment of the historical credibility of his work on heresies.